Multilevel DC Link Inverter with Reduced Number of Switches and Batteries - Y. R. Manjunatha; Anand B A (Institute of Advanced Engineering and Science, 2014)
Multilevel inverters are the best solution for medium and high voltage power electronic drives. Because of its unique characteristic of synthesizing sinusoidal voltage with less harmonic contents using several DC sources. In a three phase multilevel inverter, each phase of a cascaded H-bridge inverter requires ‘n’ DC sources to obtain 2n + 1 output voltage levels. One particular disadvantage is that, it increases number of power semiconductor switches. To overcome this disadvantage a multilevel DC link inverter (MLDCLI) with reduced number of switches and batteries is proposed.DOI: http://dx.doi.org/10.11591/ijpeds.v4i3.4618